SmartEN: A marie curie research framework for wireless sensor networks in smart management of the human environment - Onoufriou, Toula; Constantinides, Anthony G.; Kounoudes, Anastasis; Kalis, Antonis (My University, 2010)
Even though there is significant research work performed in the fields of wireless sensor networks, civil infrastructure reliability and management, most of the work is fragmented and there is no significant activity in performing multidisciplinary structured research for developing integrated smart and dynamic systems for effective management of the built and natural environment. The aim of SmartEN is to push innovation through the development of a research training network that will focus on the development and effective integration of emerging technologies targeting key application areas of current interest to Europe and the world. Institute for Computer Sciences, Social-Informatics and Telecommunications Engineering 2010.
Keywords: Application area; Civil infrastructures; Effective management; Emerging technologies; Human environment; Infrastructure reliability; Natural environments; Proactive management; Training network; Wireless sensor; Engineering research; Experiments; Innovation; Network management; Research and development management; Sensors; Signal processing; Wireless sensor networks